DAMPAK KUNJUNGAN WISATAWAN TERHADAP PENDAPATAN ASLI DAERAH KOTA MANADO DENGAN ANALISIS STATISTIK, TREN DAN PROPORSI - Lakat, Junior; Soewignyo, Fanny (FEB Universitas Sam Ratulangi Manado, 2024)
The study aims to analyze the impact of the number of tourist visits on the original income of the City of Manado in 2019-2021 as well as the trend and proportion of restaurant tax receipts in Manado City. The study uses restaurant tax realisation as a moderation variable. This is due to the presence of the Covid-19 pandemic in the period 2019-2021 which caused the number of tourist visits to the City of Manado to be disturbed. Furthermore, when the tourist visit is moderated by the realisation of restaurant tax it was found to strengthen the influence of tourists visits on Manado City PAD. This is because of the reception of the restaurant tax to be one of the largest types of tax contributors in Manado City.